MATHEMATICAL MODEL OF THE TSAGI’S TRANSONIC WIND TUNNEL T-106 AS A MACH NUMBER CONTROL OBJECT - K. D. Bukharov; V. V. Petronevich; P. V. Savin (Научный вестник МГТУ ГА, 2016)
In this paper we propose a method of constructing a mathematical model of the TsAGI’s compressor transonic wind tunnel T-106 as a Mach number control object. The mathematical model is sought in the form of a family of linear transfer functions with constant coefficients and delay. Experimental investigation of dynamic properties of the wind tunnel T-106 as an object of Mach number control in the subsonic range is provided. The coefficients of the mathematical model of the wind tunnel T-106 is identified on basis the experimental data.